Bridging Traditional and AI-Supported Arabic Language Learning: Evidence from Gallery Walk Activities among Young Learners - Asyah Mutina; Mochamad Hasyim; Syarifuddin (Universitas Islam Negeri Madura, 2026)
Foreign language anxiety is one of the affective factors that frequently hinders the success of Arabic language learning, particularly in speaking skills (maharah kalam). High levels of anxiety may reduce students’ participation in communicative activities and negatively affect their speaking performance. This study aimed to examine the effectiveness of the Gallery Walk method in reducing foreign language anxiety and improving the Arabic speaking skills of third-grade students at MI Miftahul Khoir 1 Karangrejo. The study employed a quantitative approach using a one-group pretest-posttest design. The participants consisted of 22 third-grade students selected through total sampling. Data were collected using a foreign language anxiety questionnaire adapted from the Foreign Language Classroom Anxiety Scale (FLCAS) and an Arabic speaking performance test. The data were analyzed using descriptive statistics, the Wilcoxon Signed Rank Test, and a paired sample t-test. The results revealed that the Gallery Walk method significantly reduced students’ foreign language anxiety (Z = -4.177; p < .001) and significantly improved their Arabic speaking skills (t = -17.648; p < .001). These findings indicate that Gallery Walk creates a more collaborative, interactive, and low-pressure learning environment that supports both affective development and speaking performance. Beyond its contribution to Arabic language instruction, the study highlights the potential of Gallery Walk as a pedagogical bridge between traditional Arabic language learning and emerging AI-supported language learning environments.